Peningkatan Kesadaran Beragama Melalui Pembelajaran Fikih Wudhu dan sholat: Studi Kasus pada Anak-anak di Desa Baru - Diyah Anggraini; Abu Yazid Raisal (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
This study aims to enhance children's religious awareness through the teaching of fiqh (Islamic jurisprudence) on wudhu (ablution) and prayer in Desa Baru, Asahan Regency. The main issue addressed is the low level of understanding among children regarding the correct procedures of wudhu and prayer, which impacts the quality of their daily worship. This research employs a qualitative approach with a case study method. Data was collected through direct observation, in-depth interviews, and documentation during the educational program implemented within the KKN activities. The research findings indicate a significant improvement in children's understanding and practice of worship after participating in the fiqh wudhu and prayer learning program. Children who previously had limited knowledge of essential aspects of wudhu and prayer became more disciplined in performing their religious duties. Additionally, there was an increase in their motivation to learn more about religion, and positive behavioral changes were observed, particularly in maintaining cleanliness before prayer and punctuality in performing prayers. In conclusion, this fiqh learning program had a positive impact on enhancing children's religious awareness in Desa Baru.